Social Administration and Societal Transformation in Uganda Today. - Mugavu, George (Kabale University, 2024)
Any attempt to divorce Social Administrators from mainstream societal arrangements aimed at causing societal transformation and development is a futile one. This is due to the fact that social administrators have historically been instrumental in working with governments around the world to ensure that societal needs at different levels are addressed to propel development. Societal transformation requires concerted efforts and this is exactly why governments have to embrace the role played Social Administrators in societal development. The researcher employed a purely critical qualitative approach in which desk research methodology was relied upon. As such secondary data was used and this data was obtained mainly from scholarly and published research articles surrounding Social administration, Social welfare, and other crucial published reports, with matters of the role of social administrators in societal transformation in Uganda today under scrutiny in which even the challenges incapacitating the social administrators from playing their roles well were also analyzed. Critical content analysis was employed in examining the roles of social administrators in Uganda and also the challenges that they face. Validity and reliability were guaranteed by paying much attention to critical conceptual clarity and interpretative rigor. In this paper I reviewed the genesis, the roles of Social Administrators, the challenges that hamper the activities the discipline of Social Administration drawing substantiations from the Ugandan experience. Connectedly, based on literature review, I further concluded that transforming the society is a holistic process which should be done involving all the relevant stakeholders at different levels especially in the community as this would be in position cause for ownership of all projects that could be set up to help the people improve their conditions of living. I also came up with some recommendations which included; the central government should strengthen the monitoring and evaluation department, integrating technology into mainstream societal development projects, continuously empowering local people and embracing the sustainable development strategies.